Implementation Of Maqashid Sharia in Employee Wages in Islamic Education Institutions - Budi Badrul Zaman; Isman; Imron Rosyadi (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to determine the implementation of maqashid sharia in providing employee wages in Islamic Education Institutions. This research method is qualitative using a case study approach with the object of research is the Islamic Education Institution Ar Rahmah Pacitan Foundation. The data collection techniques were carried out by observation, interview, and documentation. The data that has been collected, arranged systematically, and analysed.  Data analysis used includes data collection, data reduction, data presentation, and verification. The results of the study explain that the provision of employee wages at the Ar Rahmah Pacitan Foundation Islamic Education Institution is carried out with a process that is by the provisions of the ijarah contract, namely; there is an agreement between the institution and employees, both in terms of obligations and rights. In terms of wages given by the principles of justice (Clear, transparent, and proportional), and feasible in the sense of fulfilling the basic needs of clothing, food, and shelter, also in accordance with (market standards) other similar institutions in the same area.  Providing employee wages at the Ar Rahmah Pacitan Foundation Islamic Education Institution has realized maqashid sharia, namely dhoruriyat al-khomsah or al-kuliyat al-khomsah including Hifz al-Din, Hifz al-Nafs, Hifz al-'Aql, Hifz al-Nasl, and Hifz al-Maal.